A network meta-analysis study of monotherapies for hidradenitis suppurativa: analyses of the current evidence base - Aditya K. Gupta; Mary A. Bamimore; Vasiliki Economopoulos; Mesbah Talukder; Vincent Piguet; Renata Magalhaes (Journal of Dermatological Treatment)
Background The number of monotherapies for hidradenitis suppurativa (HS) has expanded. However, the efficacy of active comparators has not been determined in head-to-head trials.Aims We conducted an NMA to determine the relative efficacy and safety of monotherapies for HS.Methods The literature was systematically reviewed to obtain data from trials that (1) were published in English, (2) investigated a systemically administered monotherapy with an immunomodulatory agent (3) randomized, and (4) quantified efficacy, at 16 weeks, insofar as the Hidradenitis Suppurativa Clinical Response 50 (HiSCR-50), Dermatology Life Quality Index (DLQI) and Numeric Rating Scale 30 (NRS30). For safety, we analyzed the occurrence of treatment-emergent adverse events (TEAEs). For sensitivity analyses, we conducted network meta-regressions adjusted for age and sex.Results We determined the efficacy of numerous regimens including those approved by the United States FDA; for instance, the FDA-approved ‘bimekizumab 320 mg every 2 weeks’ was more efficacious than ‘IFX-1 800 mg every 2 weeks’ (odd ratio = 1.99, 95% credible interval: 1.09,3.87, p < 0.05) in terms of HiSCR-50. Sensitivity analyses showed that the main analyses were robust. Overall, risk of bias across studies was low.Conclusions The current NMA provides comparative evidence on systematic immunomodulatory HS monotherapies from the most up-to-date trial evidence.